2001
DOI: 10.1023/a:1008318614461
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinase expression and prognosis in soft tissue sarcomas

Abstract: These prognostic markers that influence growth and spread of tumor cells might be useful to define tumor aggressiveness and risk of the metastasic event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 13 publications
3
63
1
2
Order By: Relevance
“…These studies did not investigate other MMPs such as another gelatinase, MMP-2. In soft tissue sarcomas, increased MMP-2 expression and lack of TIMP-2 expression have been reported to be significant factors for poor prognosis (16). The present study analyzed for the first time the expression of not only MMP-9 but also MMP-2, MT1-MMP and TIMP-2 in osteosarcoma tissues immunohistochemically and their correlation to clinical outcome.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These studies did not investigate other MMPs such as another gelatinase, MMP-2. In soft tissue sarcomas, increased MMP-2 expression and lack of TIMP-2 expression have been reported to be significant factors for poor prognosis (16). The present study analyzed for the first time the expression of not only MMP-9 but also MMP-2, MT1-MMP and TIMP-2 in osteosarcoma tissues immunohistochemically and their correlation to clinical outcome.…”
Section: Discussionmentioning
confidence: 90%
“…Their expressions are associated with tumor invasion and increased metastatic potential (11)(12)(13)(14)(15). In soft tissue sarcomas, MMP-2 reactivity and lack of TIMP-2 expression is correlated with poor prognosis (16). However, although several studies concerning MMP-9 expression in osteosarcoma patients have been conducted (17,18), MMP-2, MT1-MMP and TIMP-2 expression have been described in only a few studies.…”
Section: Increased Expression Of Membrane-type Matrix Metalloproteinamentioning
confidence: 99%
“…Increased levels of matrix metalloproteinase-2 (MMP-2), MMP-9, and urokinase plasminogen activator appear to confer a worse prognosis, whereas increased levels of tissue inhibitor of metalloproteinase-2 (TIMP-2) are associated with improved outcomes. [18][19][20] Several groups have evaluated circulating proangiogenic and antiangiogenic factors in patients with soft-tissue sarcoma. In 1 small series of 46 patients, serum VEGF levels measured by ELISA did not differ between patients with soft-tissue sarcoma and healthy controls.…”
Section: Soft-tissue Sarcomamentioning
confidence: 99%
“…Caudroy et al showed in vitro that EMMPRIN producing tumors can stimulate MMPs both in the stroma and in the tumor cells, thus promoting tumorigenesis and metastasis (26). Another study in ovarian carcinoma showed coexpression of an EMMPRIN and MMP-1, -9 and correlated this with poor survival (27).…”
Section: Discussionmentioning
confidence: 90%
“…Benassi et al studied MMP-2, -9 and TIMP-2 expression as a prognostic indicator in STS using the non-quantitative methods of immunohistochemistry and immunoblotting (27). Their study used frozen and paraffin-embedded tumor samples from 29 liposarcomas, 29 synovial sarcoma cases and 15 malignant peripheral nerve sheath tumors and found a correlation between elevated MMP-2 activity and increased disease-free survival (p=0.0005).…”
Section: Discussionmentioning
confidence: 99%